2020
DOI: 10.1177/1129729820904599
|View full text |Cite|
|
Sign up to set email alerts
|

Patency and functionality of radiocephalic arteriovenous fistulas with an external support device (VasQ™): Real-world single-center experience

Abstract: Background: The VasQTM device was designed to improve the outcome of arteriovenous fistulae by optimizing the hemodynamics of the flow in the juxta-anastomotic region of the arteriovenous fistulae through tailored external support. The aim of the study was to evaluate the impact of the VasQ on outcome of radiocephalic arteriovenous fistulae in a real-world setting. Methods: This was a single-center, retrospective analysis of patients with either fistula creation before or after dialysis initiation with implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 20 publications
4
23
0
Order By: Relevance
“…AVF creation with the use of VasQ™ was performed as previously described and according to the surgeons' standard practice 5,6 . Typically, the procedures using the VasQ TM device do not differ from those created without the device: the device can be used in all patients except of those with known nitinol allergy, and the length of the incisions are not affected by the device.…”
Section: Surgical Procedures and Outcome Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…AVF creation with the use of VasQ™ was performed as previously described and according to the surgeons' standard practice 5,6 . Typically, the procedures using the VasQ TM device do not differ from those created without the device: the device can be used in all patients except of those with known nitinol allergy, and the length of the incisions are not affected by the device.…”
Section: Surgical Procedures and Outcome Evaluationmentioning
confidence: 99%
“…VasQ TM device has recently demonstrated benefits in reducing the risk of stenosis while promoting outward (dilative) remodeling of the outflow vein for in a set of brachiocephalic AVFs (BCAVF) 4,5 . Similar results were observed for radiocephalic AVFs (RCAVF) supported by VasQ™ in a single-center, retrospective comparative study, showing consistent outcomes for different types of AVFs 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The global epidemic of CKD and kidney failure has ignited several interesting developments that are in the pipeline. Projects that have progressed to clinical studies include a 1) pneumatic compression device (Fist Assist [Fist Assist Devices, LLC]) to promote AVF maturation 44 ; 2) the VasQ (Laminate Medical Technologies) device to improve primary AVF maturation, which regulates blood flow by constraining and shaping the fistula and reinforcing and shielding the perianastomotic vein against high pressure, wall tension, and flow levels 45,46 ; 3) the av-Guardian (Advent Access) vascular access system to guide cannulating needles into the AVF 47 ; and 4) BioNanomatrix gel (Endomimetics), designed to prevent intraluminal tissue growth and prevent stenosis in the vein segment of the AVF to promote the AVF maturation process and reduce the primary failure rate. 48 Summary After several decades of dormancy, innovations in HD vascular access have been reinvigorated.…”
Section: Innovations In the Pipelinementioning
confidence: 99%
“…Overall, our preliminary results are encouraging, especially for RCAVFs, even if with a small study population (6/16 patients). Recently, Shahverdyan et al 18 reported the impact of the VasQ on outcome of RCAVFs in a retrospective study: AVFs primary and secondary patency at 6 months were 79% and 90%, respectively; successful maturation was achieved in 88% (29/33). This is of note, because RCAVFs are associated with lower patency and maturation rates than BCAVFs.…”
Section: Discussionmentioning
confidence: 99%